1980
DOI: 10.1017/s0305000900002610
|View full text |Cite
|
Sign up to set email alerts
|

Complex sentences: acquisition of syntactic connectives and the semantic relations they encode

Abstract: The acquisition of connective forms and the meaning relations between connected clauses in the development of complex sentences is described for four children from two to three years of age. The major results of the study include the developmental interactions between syntactic connectives and meaning relations, and between these interactions and the discourse environments in which they occurred. The first syntactic connective the children learned, and, was the most general: semantically, and was used to encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
181
0
26

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(225 citation statements)
references
References 13 publications
14
181
0
26
Order By: Relevance
“…Note that the presence of two-clause matrix-subordinate structures in the child data may also be affected by syntactic complexity. Spontaneous speech studies show that the syntactic mechanisms to produce such structures emerge between 3 and 4 years in the languages in question (Aksu-Koç & Slobin, 1985;Bloom, Lahey, Hood, Lifter, & Fiess, 1980;Clancy, 1985;Clancy, Jacobsen, & Silva, 1976;Clark, 2003), so the children in our study may not yet have full mastery of them.…”
Section: Predictionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Note that the presence of two-clause matrix-subordinate structures in the child data may also be affected by syntactic complexity. Spontaneous speech studies show that the syntactic mechanisms to produce such structures emerge between 3 and 4 years in the languages in question (Aksu-Koç & Slobin, 1985;Bloom, Lahey, Hood, Lifter, & Fiess, 1980;Clancy, 1985;Clancy, Jacobsen, & Silva, 1976;Clark, 2003), so the children in our study may not yet have full mastery of them.…”
Section: Predictionsmentioning
confidence: 83%
“…Data from English spontaneous speech reveal similar patterns. Bloom et al (1980) found that and is the first clausal conjunction acquired in English, used with many different functions. Its first temporal uses, expressing sequencing and simultaneity, appear around 2;4 (note that such constructions would be classified as Loose in our study).…”
Section: Universal Patterns In Syntactic Packaging Of Manner and Pathmentioning
confidence: 99%
“…Clauses were judged as additive more often with and (vs. without and), and as contrastive more often with but (vs. without but; Segal et al, 1991). Studies on language development further suggested that and is learned earlier (25-27 months) than but (32-38 months, see, e.g., Bloom, Lahey, Hood, Lifter, & Fiess, 1980). And encoded mostly additive relations in child speech (followed by temporal, causal, and adversative relations), while but appeared with contrastive meaning.…”
Section: Conjunction Meaning and Typementioning
confidence: 99%
“…Moreover, the use of epistemic markers (i.e., markers indicating the speaker's stance towards the truth or falsehood of an utterance; e.g., 'may well' (zal wel), 'probably' (waarschijnlijk), 'then it means that' (dan betekent dat)) helps to boost the production of epistemic relations, both for children and adults. It has been stated in the literature (Bloom, Lahey, Hood, Lifter, & Fiess, 1980;Evers-Vermeul, 2005;Kyratzis et al, 1990) that content relations are acquired before epistemic relations. Verbrugge (2007) has added that even in the later phases of language acquisition (9 until 12 years old) children still have a clear preference for content conditionals.…”
Section: Connectives and Epistemic Modal Markersmentioning
confidence: 99%